Leszka Kołakowskiego rozumienie Akwinaty - Pinio, Łukasz (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
Leszek Kolakowski at first saw in the thought of Thomas Aquinas a kind of political philosophy that sacralized ecclesiastical power structures. The metaphysics of second causes was supposed to philosophically justify that reality is completely subordinate to God, whose only representative is the institution of the Church. Similarly, the epistemological postulates of Thomism, describing the relationship between faith and knowledge, were intended to emphasize the supremacy of claims derived from Revelation - while maintaining the slight autonomy of the particular sciences. In later years, Kolakowski was able to look at Thomas in a more objective way, cutting himself off from his earlier ideological assessment. The metaphysics of second causes, already non-politically interpreted, allows to justify the relative autonomy of created reality. Also, the relationship of knowledge and faith is based on methodological independence and tensions arise when cognitive competence is exceeded.